STUDIES ON NUCLEI USING CORRELATED CYTOCHEMICAL, LIGHT, AND ELECTRON MICROSCOPE TECHNIQUES - Moses, Montrose J. (The Rockefeller University Press, 1956)
In this paper, a procedure for correlating electron microscope and light microscope cytochemical studies using immediately adjacent serial thin and thick sections has been described and discussed. This technique, combined with the Feulgen reaction for DNA, has been of particular value in framing and answering both general and specific questions about the nucleus. The results may be summarized as follows:— Apparent nuclear homogeneity in the electron microscope is not due to loss of DNA as evidenced by positive Feulgen reactions in such nuclei. Arrangement of Feulgen-positive material in chromosomes, heterochromatin, perinuclear and perinucleolar chromatin, etc., is similar to that customarily observed in the light microscope but this is not necessarily reflected in a cursory survey of the electron image. Careful comparison of light and electron images shows that fine differences in structure are associated with chromatin localization. Primary spermatocyte prophase chromosomes of crayfish have been positively identified by their Feulgen-positive nature. Core-like axial structures in such chromosomes have been observed (9) and are described further. A remarkable feature of spermiogenesis in the crayfish is an elaboration of the nuclear envelope of the spermatid accompanying the formation of what becomes a mass of convoluted membranes in the sperm. In the spermatid, perinuclear chromatin follows outpocketings of the nuclear envelope into the cytoplasm. In the early sperm, on the other hand, although the nuclear envelope is continuous with the system of convoluted membranes, the chromatin is distinct from it and is retained in the nucleus proper by some mechanism independent of the nuclear envelope. None of the above observations was apparent from the electron microscope images alone; they were possible only by virtue of the correlated cytochemical and electron microscope study of adjacent sections. The successful use of other cytochemical tests, such as the PAS reaction for certain carbohydrates, in such correlated studies is also described.